Ventilation of semi-basement car parking areas - Chuan, Kian Heng. (2008)
Ventilation design of basement car park in Singapore was first studied, through a review of the relevant literature, as well as ventilation requirement in other countries. The general requirement is to provide six air changes per hour in the space and that fifty percent of the air exhausted from the space must be at a height of not more than 650 mm from the floor level.